2002
DOI: 10.1097/00004032-200204000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence and Risk Estimation Among Medical X-Ray Workers in China, 1950–1995

Abstract: Cancer incidence (1950-1995) among 27,011 medical diagnostic x-ray workers was compared by means of O/E system with that of 25,782 other medical specialists employed between 1950 and 1980 to provide evidence of human malignant tumors produced by protracted and fractionated exposure to ionizing radiation and to assess resultant cancer risk. Significant cancer risk was seen among diagnostic x-ray workers (RR = 1.2, 95% CI: 1.1-1.3). Significantly elevated risks were found for leukemia and cancers of skin, female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
108
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 29 publications
8
108
2
1
Order By: Relevance
“…29,30 However, only 2 other studies of medical radiation workers included sufficient numbers of females to enable an evaluation of the effects of chronic lowto-moderate doses of radiation on breast cancer. A study of Chinese medical radiation workers (n ϭ 27,011 total, including 5,443 females) found a significantly increased incidence risk of breast cancer among females overall (RR ϭ 1.34), 7 while a small Danish study (n ϭ 4,151 total, 82% female) observed no evidence of elevated risk of breast cancer. 10 Our results for the radiogenic leukemias are generally consistent with the body of evidence for radiation effects associated with this 1 All relative risks were stratified for attained age, calendar year of follow-up, race and gender, and adjusted for employment in other time periods.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…29,30 However, only 2 other studies of medical radiation workers included sufficient numbers of females to enable an evaluation of the effects of chronic lowto-moderate doses of radiation on breast cancer. A study of Chinese medical radiation workers (n ϭ 27,011 total, including 5,443 females) found a significantly increased incidence risk of breast cancer among females overall (RR ϭ 1.34), 7 while a small Danish study (n ϭ 4,151 total, 82% female) observed no evidence of elevated risk of breast cancer. 10 Our results for the radiogenic leukemias are generally consistent with the body of evidence for radiation effects associated with this 1 All relative risks were stratified for attained age, calendar year of follow-up, race and gender, and adjusted for employment in other time periods.…”
Section: Discussionmentioning
confidence: 95%
“…Excess risks of leukemia have been reported among male Japanese technologists employed during 1918 -1971 8 and among Chinese medical radiation workers exposed during 1950 -1985. 7 Elevated risks of leukemia were also observed among nuclear workers who were similarly exposed to chronic doses. 31 Unlike our study, cancer risk estimates for nuclear workers have been linked with individual dose measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cohort studies of electrical and electronics workers [146,203,220] along with at least one case-control study [179] have also shown elevated risks for melanoma. It has been hypothesized that workers in occupations exposed to ionizing radiation might also be at increased risk of melanoma [3,71,218,238,252].…”
Section: Occupation and Melanomamentioning
confidence: 99%